In Vitro Cholesterol-Lowering Mechanisms Of Selected Lactobacillus And Bifidobacterium Species And Effects Of Physical Treatment - Lye, Huey Shi (2013)
Fifteen strains of Lactobacillus and Bifidobacterium were screened based on their adherence property. Lactobacillus acidophilus BT 1088, L. acidophilus FTCC 0291, L. bulgaricus FTCC 0411, L. bulgaricus FTDC 1311, and L. casei BT 1268 showed higher adherence property compared to other strains studied and were thus selected for examination on cholesterol removal. Cholesterol removal ability was conducted in vitro, under conditions that mimic the human gastrointestinal tract (pH 8.0). This study provided experimental evidence to strengthen the hypothesis that lactobacilli could remove cholesterol via different mechanisms, namely assimilation of cholesterol during growth, binding of cholesterol to cellular surface, disruption of cholesterol micelle, incorporation of cholesterol into the cellular membrane, deconjugation of bile salt, bile salt hydrolase (BSH) activity, and conversion of cholesterol to coprostanol. Among the mechanisms studied, cholesterol incorporation mechanism was more prominent and the locations of incorporated cholesterol have also been identified. Considering that incorporation of cholesterol into the cellular membrane involves membrane permeability, thus sub-lethal physical treatments such as ultrasound (20-100 W; 1-3 min), electroporation (2.5-7.5 kV cm-1; 3-4 ms), and UV radiation (UVA-UVC, 30-90 J m-2) were applied with the objective to further increase cholesterol removal by Lactobacillus species.